Rasionalitas Penggunaan Kecerdasan Buatan Pada Aplikasi Kesehatan - Rowega Havaz (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This research aims to analyze in more depth the issue of implementing artificial intelligence in health applications which focuses on losses if they arise because of it. This research uses normative juridical methods, data collection techniques using literature studies where meta data is taken from books, online journals and references. other secondary. This research was analyzed using legal certainty theory, rationality theory, and responsibility theory which aims to provide an explanation from a legal perspective.